Effects of tillage managements and maize straw returning on soil microbiome using 16S rDNA sequencing. Issue 6 (9th May 2019) - Xia, Xinyao; Zhang, Piaopiao; He, Linlin; Gao, Xingxing; Li, Weijun; Zhou, Yuanyuan; Li, Zongxin; Li, Hui; Yang, Long
Abstract: Agricultural practices could affect bacterial diversity and community structure by altering soil physical and chemical properties. Straw returning and tillage practices are widely used in agriculture, however, the effects of these agricultural practices on microbiomes are still unclear. In the present study, we compared the 18 bacterial communities of soil with different straw returning and tillage treatment combinations. The V3–V4 regions of the 16S ribosomal RNA were amplified and analyzed by high‐throughput sequencing technology. The results showed that the bacterial communities were consistently dominated by Acidobacteria, Proteobacteria, Actinobacteria, and Chloroflexi . Short‐term straw returning and tillage practices significantly altered the diversity, relative abundance and functions of the soil microbiome. Soil subjected to rotary tillage and straw returning (RTS) combination possessed the highest bacterial diversity and lowest ratio of G+/G‐ bacteria, indicating that RTS could be an efficient integrated management system to improve microbiome in the short term. Double verifications based on relative abundance and network analysis, revealed close relationships of Mycobacterium and Methylibium with RTS, indicating they could serve as biomarkers for RTS. Investigating microbial changes under different agricultural practices will provide valuable foundations for land sustainable utilization and increase crop yields. Abstract : This study found that soil tillage managements and straw returning could significantly change the microbiome, based on the next‐generation sequencing technology. Several bacteria showed close relationship with the agricultural managements and could serve as the biomarkers.